2020
DOI: 10.3390/ma13225242
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Biocompatibility of Calcium Silicate-Based Sealers and Epoxy Resin-Based Sealer on Human Periodontal Ligament Stem Cells

Abstract: The aim of this study was to evaluate the biocompatibility of calcium silicate-based sealers (CeraSeal and EndoSeal TCS) and epoxy resin-based sealer (AH-Plus) in terms of cell viability, inflammatory response, expression of mesenchymal phenotype, osteogenic potential, cell attachment, and morphology, of human periodontal ligament stem cells (hPDLSCs). hPDLSCs were acquired from the premolars (n = 4) of four subjects, whose ages extended from 16 to 24 years of age. Flow cytometry analysis showed stemness of hP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 27 publications
(44 reference statements)
6
28
2
1
Order By: Relevance
“…Two additional studies which met the inclusion criteria were found during the manual search of the references of the included studies. All 20 of the resulting studies were considered as eligible for qualitative synthesis after full-text evaluation (Collado-González et al, 2017a,b;Rodríguez-Lozano et al, 2017;Wang et al, 2018;Luo et al, 2018;Collado-González et al, 2019;Rodríguez-Lozano et al, 2019a,b;Lee et al, 2019;López-García et al, 2019Abuarqoub et al, 2020;Oh et al, 2020;Olcay et al, 2020;Rodríguez-Lozano et al, 2020a,b;Zheng et al, 2020;Gaudin et al, 2020;Sanz et al, 2020c;Jing et al, 2020).…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two additional studies which met the inclusion criteria were found during the manual search of the references of the included studies. All 20 of the resulting studies were considered as eligible for qualitative synthesis after full-text evaluation (Collado-González et al, 2017a,b;Rodríguez-Lozano et al, 2017;Wang et al, 2018;Luo et al, 2018;Collado-González et al, 2019;Rodríguez-Lozano et al, 2019a,b;Lee et al, 2019;López-García et al, 2019Abuarqoub et al, 2020;Oh et al, 2020;Olcay et al, 2020;Rodríguez-Lozano et al, 2020a,b;Zheng et al, 2020;Gaudin et al, 2020;Sanz et al, 2020c;Jing et al, 2020).…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…Clinically, since CSCs/ CSSs are applied directly after mixing (before setting), the use of freshly mixed (unset) material eluates can better predict the initial response of dental stem cells towards them. Nevertheless, the use of incubated (set) material eluates could be useful to predict the late/long-term response after cellular renewal (Oh et al, 2020). The physicochemical differences between both types of sample preparations, such as pH (Pedano et al, 2018), may lead to different results in biological assays.…”
mentioning
confidence: 99%
“…В исследовании H. Oh еt al. (2020) материал на основе эпоксидных смол показал низкий остеогенный потенциал, а также препятствие заживлению костной ткани при выведении за верхушку [11].…”
Section: биосовместимость и цитотоксичностьunclassified
“…Therefore, slight moisture in root canal dentin may be advantageous to sealing, but resin-based sealer is affected by it [ 3 ]. Furthermore, several studies showed that MTA-based sealers have higher biocompatibility compared to resin-based sealers [ 4 , 5 , 6 ]. However, it is generally known that MTA has limited antimicrobial effects against some microorganisms [ 7 ].…”
Section: Introductionmentioning
confidence: 99%